The Association of PTPN22 R620W Polymorphism Is Stronger with Late-Onset AChR-Myasthenia Gravis in Turkey - DİRESKENELİ, RAFİ HANER (PUBLIC LIBRARY SCIENCE, 2014)
A functional single nucleotide polymorphism (SNP) of the PTPN22 gene encoding a protein tyrosine phosphatase has been associated with autoimmune disorders including myasthenia gravis (MG). As the PTPN22 R620W polymorphism has a wide variation of allele frequencies among different populations, this polymorphism was investigated in MG in Turkey. An emphasis is put on MG subgroups according to autoantibody (Abs) production and presence of thymoma. DNA samples from 416 patients with clinically diagnosed generalized MG (231 with Abs to acetylcholine receptor, AChR-MG), 53 with Abs to muscle-specific kinase (MuSK-MG), 55 patients with no detectable Abs (SN-MG), 77 patients with thymoma (TAMG) and 293 healthy controls (HC) were genotyped for the SNP (PTPN22 R620W, C1858T, rs2476601). The PTPN22 T allele was increased in AChR-MG patients (odds ratio [OR]: 2.5, 95%CI: 1.2-5.1). The association was stronger in late disease-onset AChR (LOMG, OR: 3.1, 95%CI: 1.2-8.2). MuSK-MG, SN-MG and TAMG groups did not carry the variant allele more frequently than the HC. In contrast to findings in other autoimmune diseases, the distribution of the PTPN22 polymorphism in this population provides a susceptibility marker for AChR-MG. The strongest association is detected in patients with LOMG.
Keywords: TYROSINE-PHOSPHATASE PTPN22; ACETYLCHOLINE-RECEPTOR; RHEUMATOID-ARTHRITIS; MULTIPLE-SCLEROSIS; GENE POLYMORPHISM; AUTOANTIBODIES; ANTIBODY; ALLELE; MUSK; FREQUENCY